Implementasi Model Limit Dan Media Pop Up Book Untuk Meningkatkan Aktivitas, Hasil Belajar Dan Keterampilan Memecahkan Masalah Di Kelas 4 Sekolah Dasar - Meta Noorrahmah; Mahmuddin (CV. ITTC INDONESIA, 2023)
The problem of this research is that students tend to be passive during the learning process, students find it difficult to solve the problems given, and student learning outcomes have not yet reached the KKM. Efforts to solve this problem using the LIMIT model. This study aims to describe teacher activities, analyze student activities, analyze problem solving skills and analyze student learning outcomes. This study used a qualitative research approach with the type of Classroom Action Research (CAR), which was carried out in four meetings. The research subjects were grade 4 students at SDN Kuin Utara 7 Banjarmasin for the 2022/2023 academic year with a total of 27 students. The types of data in this study are qualitative and quantitative data. Qualitative data were obtained through observing teacher activities and student activities. Quantitative data was obtained through measurement techniques with individual written tests. The results of this study indicate that teacher activity at meeting 4 gets a score of 26. Student activity at meeting 4 reaches 88.9% (classical). Problem solving skills at meeting 4 reached 88.9% (classical). Cognitive aspect learning outcomes at meeting 4 reached 88.9% (classical). The affective aspect learning outcomes at meeting 4 got 85.2% (classical). The results of learning the psychomotor aspects at meeting 4 got 88.9% (classical).